2023
DOI: 10.1038/s41598-023-34113-y
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of taste perception, food neophobia and oral microbiota composition in children with food allergy

Abstract: Currently, the mechanisms underlying sensory perception and sensory performance in children with food allergies are far from being understood. As well, only recently, single research afforded the oral host-commensal milieu, addressing oral microbial communities in children with peanut allergies. To bridge the current gaps in knowledge both in the sensory and microbial fields, a psychophysiological case–control study was performed in allergic children (n = 29) and a healthy sex-age-matched control group (n = 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…The next step was to experimentally evaluate the efficiency of the selected qPCR protocols (3 based on the 16S and one on the 23S gene, Table S1) on the collection of salivary DNA previously characterized by 16S metagenomics by (D’Auria et al 2023). In that paper, the authors found that the saliva of children suffering from food allergy, compared to matched controls, was enriched in “ Ca.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The next step was to experimentally evaluate the efficiency of the selected qPCR protocols (3 based on the 16S and one on the 23S gene, Table S1) on the collection of salivary DNA previously characterized by 16S metagenomics by (D’Auria et al 2023). In that paper, the authors found that the saliva of children suffering from food allergy, compared to matched controls, was enriched in “ Ca.…”
Section: Resultsmentioning
confidence: 99%
“…The latter are V3-V4 primers commonly used in 16S rRNA metagenomic studies. We used this pair in our previous work on the salivary microbiota of allergic children (D’Auria et al, 2023). The other pairs have been designed for qPCR and were included in the present study for the reasons detailed below.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations